2018
DOI: 10.1002/jclp.22611
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Outcome Questionnaire‐45.2 in outpatient anxiety clinics: A comparison between anxiety patients with and without co‐occurring depression

Abstract: Findings suggest that the OQ-45 may not adequately capture anxiety symptoms and are discussed in terms of diagnostic screening and assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This latter result requires some consideration. One potential explanation of this result is offered by Levy et al (2018), which showed that most of the anxiety-specific measures they investigated failed to predict the OQ-45 psychological distress score after controlling for depression, thus concluding that this instrument is more capable of capturing depressive symptoms than anxiety symptoms. We can also reflect on the different characteristics of the dimensions investigated.…”
Section: Discussionmentioning
confidence: 99%
“…This latter result requires some consideration. One potential explanation of this result is offered by Levy et al (2018), which showed that most of the anxiety-specific measures they investigated failed to predict the OQ-45 psychological distress score after controlling for depression, thus concluding that this instrument is more capable of capturing depressive symptoms than anxiety symptoms. We can also reflect on the different characteristics of the dimensions investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Operationalizing premature termination as termination before achieving predetermined levels of statistical change on outcome measures relies on symptom reduction to define improvement; however, a number of clients may come to therapy with goals not necessarily related to symptom reduction. This study utilized the OQ-45 to capture change across a wide variety of clinical concerns; while the OQ-45 is a strong transdiagnostic outcome measure, concerns have been raised about its ability to assess anxiety symptoms (Levy et al, 2018). Future studies should aim to collect larger samples of clients with treatment history as well as gather more detailed data regarding prior therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The body of research examining predictors of premature termination has utilized inconsistent definitions of premature termination, which has complicated the interpretation of conflicting findings (Hatchett & Park, 2003). The complexity in defining premature termination stems, in part, from the need to determine whether to prioritize client-rated, therapist-rated, or objective measures of therapy outcome (Levy et al, 2018). Many studies have identified clients as terminating prematurely if they attended fewer than a specified number of sessions, but the cutoff number used has varied widely.…”
mentioning
confidence: 99%